The relationships between interracial interaction, intercultural sensitivity and interracial bridging social capital of university students - Tamam, Ezhar (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
In this study, the author examined the relationships between interracial interaction, intercultural sensitivity, and interracial bridging social capital among Malaysian students of difference races at a Malaysian public university. Results of the regression analysis revealed that, while intercultural interaction and intercultural sensitivity are significantly correlated with interracial bridging social capital at bivariate level, only intercultural sensitivity has a direct correlation and significantly predicted interracial bridging social capital. Implications of the findings are discussed in the paper.